Investigating maize inbred line responses following infection by the Mycotoxigenic fungus Fusarium verticilliodes - Rose, Lindy Joy (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhDAgric)--Stellenbosch University, 2016.